2018
DOI: 10.1186/s13046-018-0915-z
|View full text |Cite
|
Sign up to set email alerts
|

Acidic microenvironment plays a key role in human melanoma progression through a sustained exosome mediated transfer of clinically relevant metastatic molecules

Abstract: BackgroundMicroenvironment cues involved in melanoma progression are largely unknown. Melanoma is highly influenced in its aggressive phenotype by the changes it determinates in its microenvironment, such as pH decrease, in turn influencing cancer cell invasiveness, progression and tissue remodelling through an abundant secretion of exosomes, dictating cancer strategy to the whole host. A role of exosomes in driving melanoma progression under microenvironmental acidity was never described.MethodsWe studied fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 50 publications
3
131
0
2
Order By: Relevance
“…However, none of the 3 miRNAs could serve as a biomarker for predicting storage lesions and monitoring the quality of RBC units. Although mature RBCs can not generate new RNA molecules and exosomal RNA molecules are possibly degraded with the extending storage time, we can find increasing of these 3 miRNAs during storage and attribute this phenomenon to the changes in microenvironment of stored RBCs which were previously reported [32], leading to the changes in contents of exosomes [13,27,29,30]. However, high abundance of exosomal miR-451a may mark it as an important regulatory miRNA in the recipients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, none of the 3 miRNAs could serve as a biomarker for predicting storage lesions and monitoring the quality of RBC units. Although mature RBCs can not generate new RNA molecules and exosomal RNA molecules are possibly degraded with the extending storage time, we can find increasing of these 3 miRNAs during storage and attribute this phenomenon to the changes in microenvironment of stored RBCs which were previously reported [32], leading to the changes in contents of exosomes [13,27,29,30]. However, high abundance of exosomal miR-451a may mark it as an important regulatory miRNA in the recipients.…”
Section: Discussionmentioning
confidence: 79%
“…However, the role and mechanisms of exosomes (RBCs-derived) in transfusion-related immunomodulation await clear elucidation. Secretion and contents of exosomes are regulated by different microenvironments [13,27,29,30]. The contents of exosomes (RBC-derived), stored in ACD-A solution, are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An acidic microenvironment promotes exosome secretion in intermediate melanomas (non‐invasive, metastatic) . When melanoma cells are exposed to exosomes produced in an acidic environment, they acquire migratory and invasive capacities, most probably due to an exchange of metastatic exosomal proteins . As a result, a meta‐analysis study identified 11 genes, which correlated with a poor prognosis .…”
Section: Exosomesmentioning
confidence: 99%
“…When melanoma cells are exposed to exosomes produced in an acidic environment, they acquire migratory and invasive capacities, most probably due to an exchange of metastatic exosomal proteins . As a result, a meta‐analysis study identified 11 genes, which correlated with a poor prognosis . The release of exosomes from human tumour cell lines derived from colon, breast and prostate cancers, osteosarcoma and melanoma was significantly increased at pH 6.5 in comparison with the control pH 7.4 .…”
Section: Exosomesmentioning
confidence: 99%
“…The tumor microenvironment thus tends to become nutrient poor, hypoxic and acidic as the metabolic demands of the tumor exceed the ability of tissue perfusion to maintain local homeostasis. Notably, multiple physiologic changes associated with the tumor microenvironment can induce cell stress pathways and increase exosome secretion rates, including hypoxia, extracellular acidification, and several proinflammatory mechanisms . Many of these processes are also known to interact, and to increase tumor resistance to cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%